Development of Interactive Learning Media on the Material of Relations and Functions in Middle School Students - Talapiu, Zulkarnain Putra; Abbas, Nurhayati; Katili, Nancy (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study intends to develop interactive learning media based on relationships and functions. The type of research used is development research that aims to produce a product. This study uses the Plomp development model. The sample of this study was eighth-grade students at Public Middle School 1 Bonepantai. The media development instruments in this study were validation sheets for media experts, validation sheets for material experts, and response questionnaire sheets for students and teachers. Data analysis uses quantitative descriptive analysis. The results of the study indicated that validation from media experts and material experts showed that the media met the criteria for being worthy of being tested. In addition, the results of the student response questionnaire on the interactive learning media developed were also positive; this can be seen from the average percentage of the student response questionnaire, which reached 90% with an excellent category, and the results of the teacher response questionnaire reached 91% with an excellent category. Therefore, interactive learning media meets practicality and learning merit criteria.